La aplicación de penas no privativas de libertad en la sustanciación del procedimiento expedito para la contravención contra la mujer o miembros del núcleo familiar, previo a garantizar las obligaciones del hogar - Carrion Diaz, Katherine Ximena (2015)
The thesis entitled; "The application of non-custodial sentences in the conduct of expedited for violation against women or household members, previous to guarantee the obligations of home procedure", is the result of a thorough investigation into question the deprivation of freedom that comes dictated by the judges or judges imposing seven to thirty days' imprisonment for the perpetrators of domestic violence grief, without observing that leave the abandoned home, and no one covers the basic needs of all days, reason is serving a sentence that does nothing to full compensation for the damage caused and its social rehabilitation, requiring that no deprivation of liberty which provides criminal comprehensive organic Code considered these cases treated mild punishment for being intrafamily offenses; consider that today the State must strive to bring families together and not separate or destroy more; therefore, the system should be changed sanction such breach imposing other sanctions requiring the offender romantically change their bad behavior and become more attached to his family, for this is necessary to incorporate current penal reform scheme in the sense that intrafamily offenses no deprivation of liberty as a medical treatment, psychological, training, program or educational courses required to perform community service, appear periodically authority, this would allow the offender to reflect and direct it to a family integration are issued. The content of the thesis has been possible through having had sufficient bibliographic material domestic and foreign authors contributed to complete the review of the literature and interview techniques and survey helped me achieve favorable results for my tabulation of field information was processed to reach verify my goals and contrast my hypothesis, with this enabled me to support my proposal to reform the Code of Integral criminal, present findings and recommendations and finally develop my project to reform the criminal regime Ecuadorian within contraventions of domestic violence, achieving successful completion of my thesis